2014
DOI: 10.1371/journal.pone.0097707
|View full text |Cite
|
Sign up to set email alerts
|

γδ T Cells Are Required for Pulmonary IL-17A Expression after Ozone Exposure in Mice: Role of TNFα

Abstract: Ozone is an air pollutant that causes pulmonary symptoms. In mice, ozone exposure causes pulmonary injury and increases bronchoalveolar lavage macrophages and neutrophils. We have shown that IL-17A is important in the recruitment of neutrophils after subacute ozone exposure (0.3 ppm for 24–72 h). We hypothesized that γδ T cells are the main producers of IL-17A after subacute ozone. To explore this hypothesis we exposed wildtype mice and mice deficient in γδ T cells (TCRδ−/−) to ozone or room air. Ozone-induced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
48
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(53 citation statements)
references
References 73 publications
(93 reference statements)
5
48
0
Order By: Relevance
“…In addition, we also gated on total and activated gd T cells and found that the total numbers of gd T cells, as well as activated gd T cells, were increased in the multiple-dosed mice compared with either the single-dosed or vehicle-only mice (see Figure E2 in the online supplement). Although we did not stain the gd T cells for IL-13 or IL-17A, activated gd T cells can produce both (29,30), and are also a possible source of both IL-13 and IL-17A. …”
Section: Cd3mentioning
confidence: 91%
“…In addition, we also gated on total and activated gd T cells and found that the total numbers of gd T cells, as well as activated gd T cells, were increased in the multiple-dosed mice compared with either the single-dosed or vehicle-only mice (see Figure E2 in the online supplement). Although we did not stain the gd T cells for IL-13 or IL-17A, activated gd T cells can produce both (29,30), and are also a possible source of both IL-13 and IL-17A. …”
Section: Cd3mentioning
confidence: 91%
“…This laboratory has previously reported that in mice, IL-17A contributes to the PMN recruitment observed following subacute O 3 exposure (0.3 ppm for 24–72 hr), at least in part via effects of IL-17A on expression of G-CSF, a PMN survival factor (Kasahara et al, 2012; Mathews et al, 2014a). Sources of IL-17A in the lung after subacute O 3 include macrophages and γδ T cells (Kasahara et al, 2012; Mathews et al, 2014a).…”
Section: Introductionmentioning
confidence: 99%
“…Sources of IL-17A in the lung after subacute O 3 include macrophages and γδ T cells (Kasahara et al, 2012; Mathews et al, 2014a). IL-23 can promote IL-17A expression in T-cells including γδ T-cells (Gaffen et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations